Green electrospinning of sustainable nanofibers: a sustainable frontier for next-generation materials - Zeeshan Khatri; Farooq Ahmed; Ick Soo Kim (Mehran University Research Journal of Engineering and Technology, 2023)
To fulfil the demand for eco-friendly nanomaterials, electrospinning offers a viable method for creating sustainable nanofibers. This mini review focuses on environmentally friendly and sustainability aspect of nanofibers produced via electrospinning. It examines difficulties and possibilities in ecologically friendly electrospinning, such as selecting environmentally friendly materials, reusing solvents, and using environmentally friendly additives. The use of biodegradable synthetic polymers, hybrid/composite nanofibers for improved performance, and natural polymers from renewable resources are only a few of the green electrospinning approaches that are covered. The review emphasises on green practices and sustainable challenges and opportunities. This review gives insight into green electrospinning techniques and the applications are also highlighted in tissue engineering, environmental remediation, energy storage, and environmentally friendly packaging. Further, the scalability, interdisciplinary cooperation, and regulatory issues are only a few of the obstacles and future directions that are discussed. A greener and more sustainable future in materials science is possible thanks to green electrospinning.